Highly defective dark TiO2 modified with Pt: Effects of precursor nature and preparation method on photocatalytic properties - Fakhrutdinova, Elena D.; Reutova, Olesia А.; Bugrova, Tatiana A.; Ovsyuk, I. Yu; Kibis, Lidiya S.; Stonkus, Olga A.; Vasilchenko, D. B.; Vodyankina, Olga V.; Svetlichnyi, Valerii A. (Transactions of Tianjin University)
The study focused on the modification with platinum of dark defective titania obtained via pulsed laser ablation. Both the method of Pt introduction and the nature of the Pt precursor were varied. All samples exhibited similar phase compositions, specific surface areas, and Pt contents. High-resolution transmission electron microscopy coupled with pulsed CO adsorption revealed increased dispersity when photoreduction and the hydroxonitrate complex (Me4N)2[Pt2(OH)2(NO3)8] were used. The sample featured a high content of single-atom species and subnano-sized Pt clusters. The X-ray photoelectron spectroscopy results showed that the photoreduction method facilitated the appearance of a larger number of Pt2+ states, which appeared owing to the strong metal-support interaction (SMSI) effect of the transfer of electron density from the electron-saturated defects on the TiO2 surface to Pt4+. In the hydrogen evolution reaction, samples with a significant fraction of the Pt2+ ionic component, capable of generating short-lived Pt0 single-atom sites under irradiation due to the SMSI effect, exhibited the highest photocatalytic activity. The 0.5Pt(C)/TiO2-Ph sample exhibited the highest hydrogen yield with a quantum efficiency of 0.53, retaining its activity even after 8 h of operation.